PCOS women show significantly higher homocysteine level, independent to glucose and E2 level - Zahra Eskandari; Rajab-Ali Sadrkhanlou; Vahid Nejati; Gholamreza Tizro (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2016)
Background: It is reasonable to think that some biochemical characteristics of follicular fluid (FF) surrounding the oocyte may play a critical role in determining the quality of oocyte and the subsequent potential needed to achieve fertilization and embryo development. Objective: This study was carried out to evaluate the levels of FF homocysteine (Hcy) in IVF candidate polycystic ovary syndrome (PCOS) women and any relationships with FF glucose and estradiol (ER2R) levels. Materials and Methods: In this case control study which was performed in Dr. Tizro Day Care and IVF Center 70 infertile patients were enrolled in two groups: comprising 35 PCOS and 35 non PCOS women. Long protocol was performed for all patients. FF Hcy, glucose and ER2R levels were analyzed at the time of oocyte retrieval. Results: It was observed that FF Hcy level was significantly higher in PCOS patients compared with non PCOSs (p<0.01). Observations demonstrated that in PCOS group, the Hcy level increased independent to ER2R, glucose levels, BMI and age, while the PCOS group showed significantly higher BMI compared with non-PCOS group (p=0.03). However, no significant differences were revealed between groups for FF glucose and ER2R levels. Conclusion: Present data showed that although FF glucose and ER2R levels were constant in PCOS and non PCOS patients, but the FF Hcy levels in PCOS were significantly increased (p=0.01).